The Effectiveness of Videoscribe Learning Media in Learning English Past Tense Material - Eka Resty Novieta Sari (Peneliti.net, 2021)
This study aims to improve learning outcomes of English by using videoscribe learning media. The subjects of this study were 30 class 1B. The object of this research was learning English past tense by using videoscribe. This research method is classroom action research using two cycles. The research will be carried out in two cycles; each cycle is planned for two meetings. Each meeting is two hours of lessons. Each cycle contains planning, action, observation, and reflection. Data collection techniques using observation, documentation and tests. The results of this study indicate that the increase in the average value of the class from the initial condition 44.16 to 78.63 and the increase in learning mastery from the initial condition of 20% increased to 93.33%.